Legal Freedom of the Press in the Configuration of Democratic Politics in the Reform Era - Mochamad Moro; Pandri Zulfikar; Rahul Khan (The International Journal of Law Review and State Administration, 2023)
The purpose and legal position of the press has two functions, namely: First, the press has become the oldest communication medium in the world. As a provider of communication sources, the press must be able to coexist with other state agencies or institutions. Both press are social institutions as well as political systems. The correlation between the parties cannot be separated from the philosophical and ideological foundations of society according to what they profess. Law is a system created by humans to control and limit human behavior so that it can always be monitored. Quoting Prof. Dissertation. Mahfud MD in the open senate session of Gadjah Mada University, 25 June 1993 he said that, the role and function of law is heavily influenced and often suppressed by the control of political influence. In Indonesia, political configurations are intertwined between democratic and authoritarian political configurations, while the characteristics of legal products follow the pattern of attraction between responsive and conservative products. The principle of democratic political configuration or the principle of authoritarian political configuration refers to three main indicators, namely the party concept and the role of parliamentary or people's representative bodies, domination by the executive branch, and freedom of the press.